Stability of Colloidal Silver Nanoparticles Synthesized with Variance Silver Ions as Antimicrobial in Cosmetic Formulation - Taufikurohmah, Titik; Gusti Made Sanjaya, I.; Baktir, Afaf; Syahrani, Achmad (Asian Journal of Chemistry, 2015)
Silver nanoparticles have been synthesized at variance silver ions and present glycerin as matrix in aqua solution in presence of buffer sodium. The silver ions concentrations are 5, 10, 15, 20, 25 and 30 ppm. This synthesis process using thermal oxidation-reduction treatment with 10 min. time control and temperature control at 100 °C. The concentration of glycerin was controlled to 1 mL and total 100 mL of solution. The silver cluster encapsulated by glycerin in the surface and glycerin form the ring above the clusters. These concentrate of silver ions are dependent with clusters form and clusters diameter, than used independent variable in this research. Characterization of colloidal silver nanoparticles used UV-visible spectrophotometer and TEM analysis. The l maximum absorption of silver nanoparticles is in the range 420-450 nm. The change of l maximum at variation of concentration give information that clusters move be bigger or smaller. Absorbance and l maximum absorption of UV-visible accordance with clusters diameter are discussed. The form and factual diameter of cluster nanoparticle observed by TEM. Future prospects of silver nanoparticle as potential antimicrobial in pharmaceutical formulation include formulation of cosmetics. That is important to study the stability of this colloidal. The stability of colloidal gate by measure l maximum absorption and absorbance are discussed. The characteristic and stability of colloidal are discussed. The colloidal with high stability is very good to prepare cosmetics formulation.